Analysis Of The Use Of Self-Protective Equipment (PPE) In Boom Baru Port Of Palembang - Yeti Komalasari (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
In an effort to implement work procedures safely and avoid working risks to loading and unloading activities, awareness of the loading and unloading workers (TKBM) is required to apply Occupational Safety and Health (K3) rules through the use of Personal Protective Equipment (PPE). The fact that occurs when this, the application of the use of Personal Protective Equipment (PPE) in loading and unloading activities at the Port is still lacking, even though the loading and unloading activities are high operational activities that can cause various risks of accidents, especially risks to occupational safety and health. The purpose of this study was to evaluate the process of implementing Occupational Safety and Health (K3) to Unloading Workers at the Boom Baru Port of Palembang through the use of Personal Protective Equipment (PPE). The study used survey questions and direct interviews in the field, followed by identification of project locations, visual surveys in the project and documentation taking in the field. Implementation of the use of Personal Protective Equipment (PPE). At the Boom Baru Port of Palembang, it has not been going well because of the lack of implementation of the supervisory function of the TKBM Cooperative and from the regulatory side of the Palembang Port Authority and Port Authority (KSOP).